RANCANG BANGUN WEBSITE DINAMIS PADA BADAN PELAKSANA PENYULUHAN DAN KETAHANAN PANGAN (BP2KP) KABUPATEN INDRAGIRI HILIR - Edi Santoso (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2016)
Various needs are propelling power of human thought to develop technologies that can provide convenience in every area of life, science and technology is developing rapidly. Development of Information Technology across the world have made human life becomes easier. One information technology is the fastest growing internet media that can be accessed from anywhere. Especially since the creation of the Internet network, communication becomes increasingly restricted and unrestricted. In line with the development of information technology, a progressive increase in computer capabilities also help to resolve the problem at the agency. Design Build Dynamic Website using PHP and MySQL. Is designed to provide information and data relating to the agency more easily and quickly.